2018
DOI: 10.1097/txd.0000000000000768
|View full text |Cite
|
Sign up to set email alerts
|

Single Graft Utilization From Donors With Severe Acute Kidney Injury After Circulatory Death

Abstract: Chronic shortages of organs for transplantation have led to the use of marginal kidneys from donors after circulatory death with acute kidney injury (AKI), but the utilization of kidneys with severe AKI is not well established. We retrospectively analyzed eight kidney transplantation (KTx) cases from donation after circulatory death (DCD) with terminal creatinine (t-Cr) concentrations higher than 10.0 mg/dL and/or oliguria for more than 5 days (AKI network criteria: stage III). Although all patients showed del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Most of these patients had good renal function after the first month of transplantation, as occurred with our patients, and adequate long-term graft survival. 12 It is possible to argue that all three donors in this study had AKI for rhabdomyolysis. In a retrospective observational study carried out by Chen et al, they analyzed 30 patients diagnosed with KDIGO III AKI kidneys during rhabdomyolysis, compared to 90 patients who received standard kidneys, and they reported that there was no statistical difference in relation to creatinine and GFR at months 2, 6, 12 and 24; there was also no difference in the incidence of rejection, 13 showing good graft function in the long term.…”
Section: Discussionmentioning
confidence: 84%
“…Most of these patients had good renal function after the first month of transplantation, as occurred with our patients, and adequate long-term graft survival. 12 It is possible to argue that all three donors in this study had AKI for rhabdomyolysis. In a retrospective observational study carried out by Chen et al, they analyzed 30 patients diagnosed with KDIGO III AKI kidneys during rhabdomyolysis, compared to 90 patients who received standard kidneys, and they reported that there was no statistical difference in relation to creatinine and GFR at months 2, 6, 12 and 24; there was also no difference in the incidence of rejection, 13 showing good graft function in the long term.…”
Section: Discussionmentioning
confidence: 84%
“…However, several experiences reported from DCD donors with pre‐arrest renal failure or prolonged warm ischemia as well as brain‐dead SCDs with high or rising SCr levels at the time of organ recovery have challenged this notion. In some instances, the use of AKI donor kidneys has been successfully extended to include selected ECDs, high KDPI donors, donors ≥ 65 years of age, and DDs on temporary renal replacement therapy 48–58 . Unfortunately, many AKI DD kidneys are declined by local centers, which results in delays in placement and increases CIT 41,59–62 .…”
Section: Discussionmentioning
confidence: 99%
“…Kidneys with acute kidney injury (AKI) from deceased donors are considered marginal donor kidneys (7)(8)(9)(10). Serum creatinine is a common clinical indicator of AKI, and the RIFLE (Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease), AKIN (Acute Kidney Injury Network), and KDIGO (Kidney Disease: Improving Global Outcomes) criteria all use it as a biomarker (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%